Association of Polymorphisms Calpastatin Gene with Body Weight of Local Sheep in Jonggol, Indonesia - Sutikno Sutikno; M Yamin; C Sumantri (Media Peternakan, 2011)
Calpastatin (CAST) gene is located on the fifth chromosome of sheep and plays important roles in formation of muscles and meat tenderness after slaughtering. Association of genetic polymorphism in the CAST gene locus MspI and NcoI with body weight was examined in local sheep from Jonggol Animal Science Teaching and Research Unit (JASTRU), Faculty of Animal Science, Bogor Agricultural University. The genotypes for CAST were determined by the PCR-RLFP method. Blood samples were collected from 264 local sheep belonging to JASTRU located in Singosari Village, Bogor District, West Java Province. Extraction of genomic DNA was based on the phenol chloroform method. CAST locus MspI had three genotypes including in MM, MN and NN with frequencies of 0.75, 0.23, and 0.02 respectively. CAST locus NcoI had two genotypes including in MM and MN with frequencies of 0.92, 0.08 respectively. Chi-square test confirmed Hardy-Weinberg equilibrium for the CAST locus MspI and NcoI. There was no significant effects (P>0.05) of CAST locus MspI and NcoI genotypes on body weight of local sheep in JASTRU.